2009
DOI: 10.1016/j.rcim.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective evolutionary simulation-optimisation of a real-world manufacturing problem

Abstract: Multi-objective evolutionary simulation-optimisation of a real-world manufacturing problem. 25(6) Robotics and AbstractMany real-world manufacturing problems are too complex to be modelled analytically. For these problems, simulation can be a powerful tool for system analysis and optimisation. While traditional optimisation methods have been unable to cope with the complexities of many problems approached by simulation, evolutionary algorithms have proven to be highly useful. This paper describes how simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The evolutionary methods can be easily applied to the design problem without setting parameters regarding design concepts and have been developing rapidly (Mobin et al , 2018) through the application in industry (Syberfeldt et al , 2009). However, they are difficult to deal with the four types of the relationships mentioned above (Figure 1), whereas the scalarization methods can derive the pareto optimal solution according to the four types using the quantitative weight, target value, constraint value, etc.…”
Section: Multi-objective Optimization Methodsmentioning
confidence: 99%
“…The evolutionary methods can be easily applied to the design problem without setting parameters regarding design concepts and have been developing rapidly (Mobin et al , 2018) through the application in industry (Syberfeldt et al , 2009). However, they are difficult to deal with the four types of the relationships mentioned above (Figure 1), whereas the scalarization methods can derive the pareto optimal solution according to the four types using the quantitative weight, target value, constraint value, etc.…”
Section: Multi-objective Optimization Methodsmentioning
confidence: 99%
“…The optimization algorithm then compares the performance of the system with the performance produced by previous permutations of the parameters in order to generate a new set of parameter values. This process continues until a stop criterion has been met, such as performing a defined number of evaluations, elapsing a specific amount of time or any userspecified criterion (Syberfeldt 2009). The framework of the SBO approach in this study is shown in Figure 1.…”
Section: Simulation-based Optimization (Sbo)mentioning
confidence: 99%
“…One special case of SMOO is deterministic multiobjective optimization (MOO), for which general formulations and computational frameworks are well-established [35,41,22]. SMOO formulations have a a wide range of applications that include finance [2], energy systems [9], chemical processes [43,37,31], transportation logistics [21], facility location [16,14], manufacturing and production planning [42], supply chain management [40], telecommunication, health care management [3,5], budget allocation [23], and project management [20]. SMOO problems present several interesting technical challenges.…”
Section: Motivationmentioning
confidence: 99%